Serum periostin levels in fibrous dysplasia: Its usefulness as disease biomarker. An exploratory study - Mastaglia, Silvina Rosana (2020)
Objective: Fibrous dysplasia (FD) is a rare, non-hereditary bone disease caused by a somatic mutation of GNAS gene. Periostin (Postn) is a new marker, linked to bone repair processes. We aimed to assess Postn sensitivity as disease activity marker of FD.Methods: An exploratory case-control study was led, with 15 FD patients, paired by age and gender with healthy subjects (controls). Postn serum levels were gauged in FD patients and controls, also according to clinical manifestation. In the same assay, with serum samples stored at -80°C, Postn was measured by the ELISA method (Sigma Aldrich; St. Louis, USA), [coefficient of variation (%CV) intra-assay <10% and interassay<12%]. Statistical analysis: an R Core Team 2018 processor wasused (https://www.R-project.org). A nonparametric test (MannWhitney)was used to compared Postn serum levels between the groups. ROC curves were used to find optimal cut-off points andanalyze Postn sensitivity (predictive value).Results: 15 FD patients (polyostotic 40%, monostotic 33% and McCune-Albright syndrome 27%), with an average age (X±DS) of 44.3±10 y. In our FD patient cohort, no statistically significantdifferences were observed between Postn and control group (FD: 51.1±10 ng/ml vs. control: 44.2±15 ng/ml; p=0.15) nor by FD clinical form (polyostotic: 51.8±9.1 ng/ml vs. monostotic:49.6±13 ng/ml; p=0.66). Figure 1 shows the ROC curve obtained and optimal cut-off points.Conclusion: Postn serum levels did not show statistically significant differences compared to control group or by clinical manifestation, showing low sensitivity as disease activity markerof FD.Funding: UBACYT 2018 (#0113).